A microservice‐based architecture for (customisable) analyses of Docker images. (17th April 2018) - Brogi, Antonio; Neri, Davide; Soldani, Jacopo
Summary: We introduce Docker Analyser, a microservice‐based tool that permits building customised analysers of Docker images. The architecture of Docker Analyser is designed to crawl Docker images from a remote Docker registry, to analyse each image by running an analysis function, and to store the results into a local database. Users can build their own image analysers by instantiating Docker Analyser with a custom analysis function and by configuring the architecture. More precisely, the steps needed to obtain new analysers are (1) replacing the analysis function used to analyse crawled Docker images, (2) setting the policy for crawling Docker images, and (3) setting the scalability options for obtaining a scalable architecture. In this paper, we also present 2 different use cases, ie, 2 different analysers of Docker images created by instantiating Docker Analyser with 2 different analysis functions and configuration options. The 2 use cases show that Docker Analyser decreases the effort required to obtain new analysers versus building them from scratch.